1988
DOI: 10.1111/j.1472-8206.1988.tb00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Prazosin on Total Plasma Digoxin Levels

Abstract: Prazosin and digoxin are frequently coadministered in clinical practice. To determine the effects of oral prazosin treatment on steady-state digoxin levels, 20 patients receiving a constant maintenance dose of digoxin, who had normal renal and liver functions and were not receiving any other treatment, were given 5 mg of prazosin for 3 days. Plasma digoxin levels were measured before, on days 1 and 3 of prazosin treatment, and after prazosin had been discontinued. It was found that prazosin significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Concomitant therapy may alter digoxin absorption, distribution, and/or excretion. Several drug interactions have recently been reported in review articles [13,30], and, among them, clinically significant ones are listed in Table 2 [31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Drug Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant therapy may alter digoxin absorption, distribution, and/or excretion. Several drug interactions have recently been reported in review articles [13,30], and, among them, clinically significant ones are listed in Table 2 [31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Drug Interactionsmentioning
confidence: 99%
“…Nifedipine [38] Prazosin [39] Propantheline [36] Quinidine [40,41] Spironolactone [42] Verapamil [43,44] [50] Increases risk of toxicity [51] Increases risk of toxicity [46] Increases risk of toxicity [48] Slightly increases risk of toxicity [49] Slightly increases risk of toxicity [61] Increases risk of toxicity [62] ably the most frequent factor contributing to digitalis toxicity• Although potassium infusions have not been shown to increase the maximum lethal dose of digoxin in experimental studies [45], and despite the fact that hypokalemia was not frequently found to be an independent risk factor for digoxin toxicity in large-scale clinical trials [5,6], there is some evidence to suggest that, in addition to having direct arrhythmogenic effects, hypokalemia decreases the threshold for digoxin toxicity [46,47]. Maintaining a serum potassium level > 4.0 mEq/L is particularly important in situations such as electrical cardioversion, where the sarcolemma is momentarily paralyzed and a loss of intracellular potassium down the chemical gradient occurs.…”
Section: -35% Decrease In Digoxin Absorptionmentioning
confidence: 99%